Hybrid material based on subgleba of mosaic puffball mushroom (Handkea utriformis) as an adsorbent for heavy metal removal from aqueous solutions. (1st November 2021) - Milošević, Dragana; Lević, Steva; Lazarević, Slavica; Veličković, Zlate; Marinković, Aleksandar; Petrović, Rada; Petrović, Predrag
Abstract: The alkali treated subglebal tissue of the mosaic puffball ( Handkea utriformis ) (Sa) and Sa modified with hydroxyapatite (Sa-HAp), obtained by successive ionic layer adsorption and reaction (SILAR) method, were used for the removal of Pb 2+, Cd 2+ and Ni 2+ from aqueous solution. The materials were characterized by FT-IR, Raman, SEM and EDS analysis and by determination of pHPZC . The adsorption performances of Sa and Sa-HAp were assessed in batch experiments at different pH, contact times, temperatures and mass of the adsorbent. Different models of adsorption isotherms were used, and the best fit was obtained with the Langmuir model. Maximum adsorption capacities of Sa towards Pb 2+, Cd 2+ and Ni 2+ were 44.82, 15.54 and 17.21 mg g −1, while for Sa-HAp were 79.55, 52.59 and 45.01 mg g −1, respectively. Kinetic data were well fitted by a pseudo second-order model, while thermodynamic studies disclose spontaneous and endothermic adsorption process. The Sa-Hap was successfully regenerated with 1 M NaCl and after the fifth desorption cycle and 10 h achieved 82.9, 69.7 and 60.4 %, while for 0.5 M NaCl + 0.5 M NaOH and 1 h was 78.3, 64.1, 57.5 % of desorbed Pb 2+, Cd 2+ and Ni 2+, respectively. The competitive study and results from a column system confirmed good applicability of Sa-HAp adsorbent. Highlights: Alkali treated subglebal tissue of the mosaic puffball ( Handkea utriformis ) (Sa) was modified by hydroxyapatite (Sa-HAp). The SILAR method was optimized to deposit a thin HAp film of a large surface area. Adsorption/desorption, kinetic and thermodynamics of Pb 2+, Cd 2+ and Ni 2+ onto Sa and Sa-Hap were investigated. Alkaline treatment increased the subgleba surface functionalities and HAp modification contributed to better adsorption.